Ultrasound-assisted dilute acid hydrolysis for production of essential oils, pectin and bacterial cellulose via a citrus processing waste biorefinery - Karanicola, Panayiota; Patsalou, Maria; Stergiou, Panagiota Yiolanda; Kavallieratou, Alexandra; Evripidou, Nikolas; Christou, Panagiotis; Panagiotou, George; Damianou, Christakis A.; Papamichael, Emmanuel M.; Koutinas, Michalis (My University, 2021)
An orange peel waste biorefinery was developed employing a design of experiments approach to optimize the ultrasound-assisted dilute acid hydrolysis process applied for production of useful commodities. Central composite design-based response surface methodology was used to approximate the combined effects of process parameters in simultaneous production of essential oils, pectin and a sugar-rich hydrolyzate. Application of a desirability function determined the optimal conditions required for maximal production efficiency of essential oils, pectin and sugars as 5.75% solid loading, 1.21% acid concentration and 34.2 min duration. Maximum production yields of 0.12% w/w essential oils, 45% w/w pectin and 40% w/w sugars were achieved under optimized conditions in lab- and pilot-scale facilities. The hydrolyzate formed was applied in bacterial cellulose fermentations producing 5.82 g biopolymer per 100 g waste. Design of experiments was efficient for process analysis and optimization providing a systems platform for the study of biomass-based biorefineries.
Keywords: Bacterial cellulose; Essential oils; Ultrasound-assisted dilute acid hydrolysis; Pectin; Orange peel waste